2012
DOI: 10.1021/ja303173n
|View full text |Cite
|
Sign up to set email alerts
|

Boundaries of Anion/Naphthalenediimide Interactions: From Anion−π Interactions to Anion-Induced Charge-Transfer and Electron-Transfer Phenomena

Abstract: The recent emergence of anion-π interactions has added a new dimension to supramolecular chemistry of anions. Yet, after a decade since its inception, actual mechanisms of anion-π interactions remain highly debated. To elicit a complete and accurate understanding of how different anions interact with π-electron-deficient 1,4,5,8-naphthalenediimides (NDIs) under different conditions, we have extensively studied these interactions using powerful experimental techniques. Herein, we demonstrate that, depending on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
238
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 346 publications
(266 citation statements)
references
References 72 publications
21
238
0
7
Order By: Relevance
“…41 Since the Lewis acidity of the NDIs was not the reported limitation for the electron transfer in this process, we predicted that thermally induced electron-transfer might also occur with the NDI units of P(NDI2OD-T2), leading to a n-doping effect.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…41 Since the Lewis acidity of the NDIs was not the reported limitation for the electron transfer in this process, we predicted that thermally induced electron-transfer might also occur with the NDI units of P(NDI2OD-T2), leading to a n-doping effect.…”
Section: Resultsmentioning
confidence: 99%
“…Irrespective of the electron depletion mode of the anion, the corresponding NDI molecule was reduced to the same radical anion product that displayed identical spectroscopic signals. 41 We note that the exact mechanism of radical anion formation is under debate, particularly with highly electronegative fluoride anions in which direct electron transfer seems thermodynamically unlikely. Nevertheless, Saha's results suggested that soluble anions might be suitable as readily available n-type dopants of polymeric NDI derivatives.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The organic ligand DPNDI was synthesized according to the same procedures reported in the literature [35]. The infrared spectra were obtained in the range of 400-4000 cm -1 from a Perkin-Elmer FT-IR spectrophotometer (Waltham, MA, USA), and powder X-ray diffraction (PXRD) were recorded on a Rigaku MiniFlex-II X-Ray diffractometer (Tokyo, Japan) using graphite-monochromated Cu Kα radiation (λ = 1.5406 Å) in the range of 5-50 • .…”
Section: Methodsmentioning
confidence: 99%